Mexican American Civil Rights in Texas - Avena, J. Richard; Brischetto, Robert R. (Book collections on Project MUSE., 2021)
"Inspired by a 1968 U.S. Commission on Civil Rights six-day hearing in San Antonio that introduced the Mexican American people to the rest of the nation, this book is an examination of the social change of Mexican Americans of Texas over the past half century with recommendations for the future of immigration, voting rights, educational equity, employment and economic security, health and the criminal justice system"--